From Policy to Practice: The Inclusive Education in Primary School No. 3 Sempidi, Mengwi - Haes, Putri Ekaresty; Dewi, Ni Luh Yulyana (Journal Corner of Education, Linguistics, and Literature, 2024)
The research was conducted at Sekolah Dasar No. 3 Sempidi Mengwi, which is located in Badung district, specifically in inclusive elementary school aims to investigate the implementation of inclusive education policies initiated by the government so that all children can receive education including children with special needs (ABK). The informants in this study focused on teachers who teach in inclusive classes, so that they can explain teaching and learning activities in inclusive classrooms. This study is a qualitative study with three data collection methods, namely participatory observation, and interviews with main informants and supporters. The data analysis technique uses a data analysis technique initiated by Miles and Huberman. The results of the research conducted for six months are (1) Sekolah Dasar No. 3 Sempidi Mengwi has implemented an inclusive education policy, although there are still many obstacles and challenges that must be addressed immediately so that the school becomes a comfortable place for all children, including students with special needs. The conclusions drawn are: Sekolah Dasar No. 3 Sempidi, Mengwi, Badung Regency need to work hard in responding to the challenges of inclusive education by providing more educational staff, child psychologists and improving school facilities and infrastructure for the comfort of all children (disabled and normal) who study at the school.